Antimicrobial Resistance, Politics, and Practice in India. (September 2020) - Broom, Alex; Doron, Assa
India is considered the epicenter of the global antimicrobial resistance crisis, with unprecedented antimicrobial consumption, production, and "misuse." But the story of resistance in India is complicated—emerging from intersections of industrial pharmaceutical development, rationing/purchasing of health care, policy infrastructure, and dynamics of disadvantage. What looks like rampant, escalating antimicrobial misuse and a need for tighter controls over drugs and "prescribers, " emerges as a complex social problem. These dimensions reach the bedside, although variously, with doctors in India dealing with precarious infectious disease landscapes, threats of multidrug-resistant organisms, and (pan) national imperatives for "more judicious" practices. Drawing on 24 semi-structured interviews with doctors in Hyderabad, we explore their perspectives on resistance (literal and figurative) in everyday practice, and how practices articulate intersections of power, influence, and governance. This offers broader context to reframe resistance in India as multifactorial, enacted through cultural/local practices, and irreducible to singular problems of control or regulation.